2021
DOI: 10.1186/s12879-021-06178-5
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative assessment in acceptability and barriers to use pre-exposure prophylaxis (PrEP) among men who have sex with men: implications for service delivery in Vietnam

Abstract: Background HIV Pre-exposure prophylaxis (PrEP) is being considered for implementation among MSM nationwide in Vietnam. However, there may be concerns about potential obstacles for PrEP adherence among Vietnamese MSM. This study aims to assess the acceptability to use PrEP, potential barriers and facilitators, and the preferences for PrEP service accessibility and delivery among Vietnamese MSM. Methods Four focus group discussions (FGDs) were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…We hypothesize that MSM patients, in addition to auto-testing more frequently, have a higher risk perception that plays an important role in the acceptance of PrEP ( Plotzker et al, 2017 ). Consistently with our hypothesis, some other studies have already reported that there is a high level of willingness and acceptance of PrEP use among MSM ( Frankis et al, 2016 ; Phan and Vu, 2017 ; Spinner et al, 2018 ; Nguyen et al, 2021 ). Moreover, in Portugal, it is known that almost the entire population interested in using PrEP is MSM; however, no such study has been published until now.…”
Section: Discussionsupporting
confidence: 92%
“…We hypothesize that MSM patients, in addition to auto-testing more frequently, have a higher risk perception that plays an important role in the acceptance of PrEP ( Plotzker et al, 2017 ). Consistently with our hypothesis, some other studies have already reported that there is a high level of willingness and acceptance of PrEP use among MSM ( Frankis et al, 2016 ; Phan and Vu, 2017 ; Spinner et al, 2018 ; Nguyen et al, 2021 ). Moreover, in Portugal, it is known that almost the entire population interested in using PrEP is MSM; however, no such study has been published until now.…”
Section: Discussionsupporting
confidence: 92%
“…In stigmatized key populations, PrEP access in key population-led community organizations is a promising way forward. In Vietnam, GBM have expressed a preference for accessing PrEP through community organizations and GBM-friendly clinics [18]. In both Vietnam and Thailand, successful PrEP roll-out programmes have been based in community-based organizations led by GBM and/or transgender women [32].…”
Section: Approaches To Increasing Preexposure Prophylaxis Uptakementioning
confidence: 99%
“…The Australian National HIV Strategy 2018–2022 includes a target of 75% of eligible people on PrEP, and the New South Wales state HIV strategy 2021–2025 targets PrEP coverage of 90% in GBM who have casual sex without condoms [17]. Vietnam is targeting 30% of GBM taking PrEP by 2025 [18]. However, most countries have not specified national PrEP targets.…”
Section: Preexposure Prophylaxis Goals and Targets: How Much Preexpos...mentioning
confidence: 99%
“…Results from two randomized controlled trials (HPTN 083 and HPTN 084) suggested an estimated 66% relative reduction in HIV risk among cisgender men and transgender women who have sex with men [ 6 ] and 88% reduction among cisgender women compared with oral PrEP [ 7 ]. Long‐acting injectable products have been found to be acceptable and often preferred in studies examining community PrEP preferences [ 8 , 9 , 10 , 11 , 12 ]. As such, CAB‐LA may reach new clients for HIV prevention and be a more acceptable choice for people who have concerns about oral PrEP or other prevention options or difficulty taking these as prescribed.…”
mentioning
confidence: 99%
“…Programmes must invest in awareness and demand‐raising activities to support introduction using positive, gain‐framing messaging to position CAB‐LA alongside other HIV prevention choices. While potential PrEP users are interested in injectable PrEP [ 8 , 9 , 10 , 11 , 12 ], it is unclear how choices will translate into the uptake of CAB‐LA and how people from different populations and geographies may choose to start, stop and restart CAB‐LA, and switch between PrEP options. Indeed, while people supported to continue CAB‐LA had high adherence to bi‐monthly injections at 91.5% and 93% for HPTN 083 and 084, respectively [ 6 , 7 ], how effective use can be supported outside trial settings remains to be determined.…”
mentioning
confidence: 99%